Drug–Drug Interactions in the Treatment of Cancer-Associated Venous Thromboembolism with Direct Oral Anticoagulants - Hellfritzsch, Maja; Henriksen, Jakob Nørgaard; Holt, Marianne Ingerslev; Grove, Erik Lerkevang (Seminars in Thrombosis and Hemostasis, 2023)
Venous thromboembolism (VTE) is a frequent complication of cancer, and management of cancer-associated thrombosis (CAT) is challenging due to increased risks of bleeding and recurrent VTE. Recent trials have shown an acceptable efficacy and safety of direct oral anticoagulants (DOACs) in the treatment of CAT compared to low-molecular weight heparin. Although DOACs provide an effective and convenient treatment option in CAT, the need to assess the risk of drug–drug interactions (DDI) with antineoplastic therapies poses a barrier to their use in clinical practice. With the aim of supporting the assessment of CAT patients for treatment with DOAC, this review provides a comprehensive overview of the compatibility of antineoplastic therapies with the individual DOACs (apixaban, dabigatran, edoxaban, and rivaroxaban). Using several data sources, we characterized 100 widely used antineoplastic agents with regard to their effect on p-glycoprotein and cytochrome P450, both important in the transport and elimination of DOACs. This enabled us to evaluate 400 “DOAC-antineoplastic agent”-pairs regarding their likelihood to interact (unlikely, potential, or likely), ultimately leading to clinical recommendations on the appropriateness of concomitant use for each pair. A potential or likely DDI was identified for 12% of the evaluated pairs. For nearly all antineoplastic agents, at least one DOAC was considered compatible.
Keywords: anticoagulants; cancer; drug interactions; venous thromboembolism